Inactivated probiotic Bacillus coagulans GBI-30 induces complex immune activating, anti-inflammatory, and regenerative markers in vitro - Jensen GS; Cash HA; Farmer S; Keller D (Dove Medical Press, 2017)
Gitte S Jensen,1 Howard A Cash,2 Sean Farmer,2 David Keller2 1NIS Labs, Esplanade, Klamath Falls, OR, USA, 2Ganeden Biotech Inc., Landerbrook Drive Suite, Mayfield Heights, OH, USA Objective: The aim of this study was to document the immune activating and anti-inflammatory effects of inactivated probiotic Bacillus coagulans GBI-30, 6086 (Staimune™) cells on human immune cells in vitro.Methods: In vitro cultures of human peripheral blood mononuclear cells (PBMC) from healthy blood donors were treated with inactivated B. coagulans GBI-30, 6086 cells for 24 hours. After incubation, the PBMC were stained with fluorochrome-labeled monoclonal antibodies for CD3, CD56, and CD69 to monitor cellular activation by flow cytometry. The culture supernatants were tested for cytokine profile using a 27-plex Luminex array, including pro- and anti-inflammatory cytokines, chemokines, and growth factors.Results: Inactivated B. coagulans GBI-30, 6086 cells induced the CD69 early activation marker on CD3+ CD56− T lymphocytes, CD3+ CD56+ NKT cells, CD3−CD56+ NK cells, and also some cells within the CD3−CD56− non-T non-NK cell subset. Culture supernatants showed robust increases in the immune-activating cytokines IL-1β, IL-6, IL-17A, and TNF-α. IFN-γ levels were increased, along with three chemokines, MCP-1, MIP-1α, and MIP-1β. The two anti-inflammatory cytokines IL-1ra and IL-10 showed increases, as well as the G-CSF growth factor involved in repair and stem cell biology. In contrast, GM-CSF levels showed a mild decrease, showing a highly selective growth factor response.Conclusion: The inactivated B. coagulans GBI-30, 6086 cells activated human immune cells and altered the production of both immune activating and anti-inflammatory cytokines and chemokines. Of special importance is the novel demonstration of a selective upregulation of the G-CSF growth factor involved in postinjury and postinflammation repair and regeneration. This suggests that important immunogenic cell wall components, such as lipoteichoic acid, are undamaged after the inactivation and retain the complex beneficial biological activities previously demonstrated for the cell walls from live B. coagulans GBI-30, 6086 (GanedenBC30) probiotic bacteria. Keywords: anti-viral, anti-inflammatory, cytokines, growth factors, lipoteichoic acid, inactivated bacillus coagulans GBI-30, 6086, Staimune